The Effect of the Application of Total Quality Management, Supply Chain Management, and Entrepreneurship Orientation on Operational Performance - Latifah, Siti Nur; Wijayanti, Wijayanti; Utami, Esti Magiyanti (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2021)
Small and medium enterprises in the food sector in the pandemic era were significantly affected, so SMEs need to improve their performance, so they are not significantly affected. This study aims to examine the effect of implementing TQM on the operational performance of Food SMEs, examining the effect of SCM application on the operational performance of Food SMEs, and examining the effect of the application of entrepreneurial orientation on the operational performance of Food SMEs in Wonosobo Regency. This study used a purposive sampling technique and obtained a total sample of 120 people. This study used a survey research design and data collection was carried out using a questionnaire. Data analysis was performed using multiple linear regression. The results of multiple linear regression and hypothesis testing show that the TQM variable has a positive and significant effect on operating performance. The SCM variable has a positive and significant effect on operating performance. The entrepreneurial orientation variable has a positive and significant effect on operating performance.